The Role of Tropical Cyclones on the Total Precipitation in Cuba during the Hurricane Season from 1980 to 2016 - José C. Fernández–Alvarez; Rogert Sorí; Albenis Pérez–Alarcón; Raquel Nieto; Luis Gimeno (Atmosphere, 2020)
This study quantifies the amount of rainfall supplied by tropical cyclones (TCs) to Cuba. It uses the long–term global gridded Multi–Source Weighted–Ensemble Precipitation (MSWEP) v2 data set, with a resolution of 0.1° in latitude and longitude, and a temporal resolution of 3 h during the hurricane seasons from 1980–2016. During this study period, 146 TCs were identified within a 500–km radius of Cuba. The contribution of TCs to the total precipitation over Cuba during the cyclonic season was ~11%. The maximum contribution occurs in October and November, representing 18% and 28% of the total precipitation, respectively. The interannual precipitation contribution shows a positive correlation (~0.74) with the number of TCs, but without a significant trend for the period. A climatological spatial analysis of the rainfall associated with TCs revealed great heterogeneity, although the major contribution was observed along the southern coast of the eastern and central provinces of Cuba, and in the western province of Pinar del Río. No significant difference was observed between the number of TCs that affected Cuba and their rainfall contribution under the positive and negative phases of the El Niño Southern Oscillation. However, the negative phase of the NAO led to an increase in the genesis of TCs that later affected Cuba, which led to a greater contribution to precipitation compared to that obtained from TCs during the positive phase of this oscillation. Our results also confirm that anomalous warmth of the tropical Atlantic Ocean, revealed through the Atlantic Meridional Mode, and enlargement of the Atlantic Warm Pool, enhances the genesis in the North Atlantic Basin of the TCs that affect Cuba, which was associated with an increase of the rainfall contribution to the total precipitation compared to that calculated for TCs formed during the opposite phases.